EXPLORING THE SYNERGY BETWEEN TEACHER ROLE, MOTIVATION, AND STUDENT PERFORMANCE IN ONLINE PRIMARY EDUCATION - Sandraitika Sari; Maximus Gorky Sembiring; Suroyo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The rapid shift to online learning has brought significant changes to teaching practices and student participation, especially in elementary education where close teacher–student interaction is crucial. Despite this shift, empirical evidence on the factors that determine the effectiveness of online learning in Indonesian elementary schools remains limited. This study aimed to analyze the influence of teacher roles, learning motivation, and learning outcomes on the effectiveness of online learning at SD Negeri 007 Sekar Mawar Air Molek. A quantitative research approach was applied, involving 147 upper-grade students as participants. Data were collected through validated Likert-scale questionnaires and analyzed using descriptive statistical techniques and simple linear regression. The results showed that teacher roles had a very strong influence on the effectiveness of online learning (R = 0.996, R² = 0.992) as well as on student learning outcomes (R = 0.999, R² = 0.997). Furthermore, learning outcomes were found to significantly contribute to online learning effectiveness (R = 0.895, R² = 0.801). These findings underline the central role of teachers as facilitators, motivators, and evaluators in creating meaningful and effective online learning experiences. In conclusion, the effectiveness of online learning in elementary schools largely depends on teacher competence, the ability to foster student motivation, and adequate technological preparedness to support sustained student achievement.